PENDEKATAN LEAN SIX SIGMA, FMEA-AHP UNTUK MENGIDENTIFIKASI PENYEBAB CACAT PADA PRODUK SANDAL DI PT. â€œXâ€ - Wibowo, Moh. Muhyidin Agus; Pratikto, Pratikto; wijayanti, widya (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2016)
Abstract Quality is one of problems commonly happen in production. It can be vary and affect the level of product quality and service. Improving quality is needed to keep a good quality of a product. X Inc is one of a company focus on making slipper. The problem is facing by the company is that the method use to decrease the defect and waste is not effective yet. Based on the problem above, a researcher conduct a research and basic concept development lean six sigma to improve the quality by integrating FMEA and AHP in identifying the product defect. It is hoped that the X inc. can keep or maintain and improve the quality in order to fulfill the costumer`s need. Based on the result of FMEA-AHP computation, it is found that IR result is 0,0745. It means that the data is consistent. While priority FMEA-AHP computation for each criteria will be used as reference in making or taking decision.Â Keywords : lean six sigma approachment, FMEA-AHP, defect, slipper.